Serum sirtuin-1 a potential marker in the diagnosis of rheumatoid arthritis - Liming Tan; Tanglin Ouyang; Xu Li; Yinyi Chen; Shipeng Ke; Jiayuan Chen; Ye Liu; Fajun Zeng; Yingxing Chen; Jing Long; Qingyue Deng; Xiaoyan Hu (Taylor & Francis Group, 2023)
Introduction: To explore the value of serum sirtuin-1 (SIRT1) in the diagnosis and evaluation of joint mobility of rheumatoid arthritis (RA). Materials and Methods: Serum was randomly obtained from 212 RA patients,210 non-RA patients and 58 healthy controls in a large tertiary first-class hospital in Jiangxi province from November 2021 to June 2022. The level of serum Sirt1,anti-cyclic citrulline polypeptide antibody (anti-CCP), anti-mutant citrulline vimentin antibody (anti-MCV), rheumatoid factor (RF),high-mobility group box 1 (HMGB1), collagen triple helix repeat containing 1 (CTHRC1), erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were detected by ELISA, to explore the correlation between them and their value in the diagnosis and evaluation of joint range of motion of RA and statistically analyse their diagnostic efficiency. Results: ① The level of all markers was higher in the RA group than in the non-RA group and the healthy controls (p < 0.05). ② The AUC of the SIRT1 was 0.882, second only to the anti-MCV and anti-CCP. ③ The anti-CCP showed the highest sensitivity to RA diagnosis of 0.948. The specificity and positive predictive value of SIRT1 for the diagnosis of RA were the highest, which are 0.959 and 0.934 respectively. ④ In serial combination, SIRT1/anti-CCP、SIRT1/anti-MCV showed the highest specificity.SIRT1/anti-CCP in parallel combination had the highest sensitivity. ⑤ SIRT1 showed a significant correlation with other markers and DAS28 scores (p < 0.01). Conclusion: SIRT1 can be used as a new serological marker for RA diagnosis, which has a significant correlation with RA joint mobility and has a certain reference value in RA differential diagnosis, providing a new detection basis for RA differential diagnosis.